중학생의 성교육 요구 - 박춘화; 박금자; Park, Choon-Hwa; Park, Geum-Ja (여성건강간호학회지, 2002)
The purpose of this study was to identify the need for sex education in middle school students Research subjects were 194 students who attended at I seminary in B city. The period of data collection was from July to August, 2001. Research instrument was composed of 61 structured items 17 items related to demographics and sex, 44 items related to the need of sex education. Data were collected through the self-report method by the researcher and one trained assistant. The instrument developed by the researchers was employed to measure the need of sex education and it's Cronbach's $α$ = 0.9349 in this research. Data were analyzed by frequency, percentage factor analysis and t-test using SPSS WIN Program. The findings of this study are summarized as follows : 1. The highest score among characteristics of sex was 'less interest about sex(42.6%)', 39.0% of subjects got information about sex from friends or elders. 52.3% of subjects consulted friends or elders about sex problems. The number of sex education lessons was 1-2 times in school during last semester (61.0%). Education by the school nurse was 35.9% to students. 43.1% of subjects announced moderate satisfaction on sex education. 2. The mean score of the need for sex education was $2.88{±}0.47$ (lowest value 1, highest 4). The most wanted sex education factor was 'chastity and sexual responsibility($3.33{±}0.67$)' and followed by 'family and marriage ($3.26{±}0.62$)' and 'considerations of sex($3.07{±}0.69$)'. Meanwhile, the lowest wanted sex education factor is 'physiological characteristics of male ($2.47{±}0.72$)', followed by 'sexual behavior ($2.49{±}0.75$)'. The most wanted sex education item was 'the meaning of family ($3.54{±}0.75$)' and followed by 'the cautions to prevention from sexual abuse ($3.49{±}0.78$)' and sexual activity and responsibility($3.43{±}0.77$)'. Meanwhile, the lowest wanted sex education item is 'masturbation ($2.16{±}0.97$)', followed by 'circumcision($2.32{±}0.97$)'. 3. There is no significant difference between boys and girls in mean score about the need for sex education(t=-.715, p=.476). Sex education factor that girl-students wanted was 'physiological characteristics of female'. Sex education factor that boy-students wanted was 'family and marriage'. Sex education items that girl-students wanted were 'cautions during menstruation', the relation of ovulation and pregnancy', caution to prevention from sexual abuse' and sexual behavior and responsibility'. Sex education items that boy-students wanted were 'the meaning of family', 'the importance of marriage', 'male's sex organs', 'a wet dream', 'the method to resolve sexual curiosity', 'sexual intercourse' and 'the connection with the other sex'. In conclusion, the mean score of the need for sex education is medium. The route to attain knowledge about sex and sexual problem is through consulting friends and elders. Therefore, it is necessary to give sex education that is suitable to the subject's needs and methods. Also, it is necessary to give differently strong point about sex education between female and male students.